A New Strategy to Pretreat Carbon Nanofiber and Its Application in Determination of Dopamine. (15th August 2010) - Liu, Dong; Liu, Yang; Hou, Haoqing; You, Tianyan
Abstract : A novel sonochemical process, using hydrogen peroxide in a laboratory ultrasonic bath, was employed to pretreat the carbon nanofiber (CNF) for creating oxygen-rich groups on the surface of CNF. After the sonochemical process, the CNF showed good hydrophilicity and high electrochemical activity. Compared to normal pretreatment process, this sonochemical process is timesaving and effective for dispersion and functionalization of CNF. The resulting CNF showed high catalytic activity toward the oxidation of DA. A carbon paste electrode modified by CNF (CPE-CNF) was used to determine the dopamine (DA) in the presence of ascorbic acid (AA). The detection limit is 0.05 μ M, with the linear range from 0.05 μ M to 6.4 μ M.